Evaluating eating patterns and health status of undergraduate students majoring in human nutrition, Lahore, Pakistan: a cross-sectional study - Saad Afzal; Ayesha Iftikhar; Mateen Ahmad; Zeeshan Ashraf; Waseem Khalid; Shinawar Waseem Ali; Maryam Illyas; Fareed Afzal; Muhammad Zubair Khalid; Tawfiq Alsulami; Emery Lenge Mukonzo (International Journal of Adolescence and Youth)
This study aims to evaluate the nutritional status of aspiring nutritionists in universities across Lahore. A cross-sectional survey was conducted using a self-administered questionnaire, and dietary analysis was done using USDA food composition tables. Results showed that 63% of participants from upper middle-class backgrounds were either obese or underweight, while 25% of those affected by malnutrition were from lower middle-class backgrounds. The average caloric intake was only 990 ± 347 kcal, which is well below the requirement for healthy adult functioning. A significant proportion of obese individuals consumed junk food daily, while all groups had inadequate intakes of protein, carbohydrates, and fats. Refined carbohydrates dominated meals, and protein sources were generally of low biological value. There was a strong association between socio-economic status and nutritional status (p < 0.005). The study concludes that nutrition knowledge alone is insufficient for promoting healthy habits targeted interventions are essential for long-term health improvements.